Can self-motion illusions (circular vection) facilitate spatial updating? - Riecke, Bernhard E.; Feuereissen, Daniel; Rieser, John J.; McNamara, Timothy P. (Spatial Cognition 2014 Conference, 2014)
Bipedal locomotion facilitates updating of spatial orientation when exploring novel or familiar large immersive virtual environments. But full body locomotion in a tracking space is costly in equipment and space. Here we investigate a method of inducing the illusion of locomotion in stationary observers and show that the illusion can also facilitate spatial updating. When we move through our surroundings, self-to-object distances and directions change dynamically, and yet we remain aware of our changing orientation even when walking in the dark or with our eyes closed. This is generally attributed to the integration of physical self motion cues with spatial representations of the surroundings, resulting in automatic spatial updating. However, we get lost far more easily when self-motion is only visually simulated (for example in virtual reality, computer games, or tele-presence applications). Allowing people to physically walk is one solution, but it is expensive in terms of the size of the physical space needed and tracking system. As a step toward addressing this challenge, we provided participants with an illusory sensation of self-motion (circular vection). We hypothesized that the illusion of self-motion could induce spatial updating just as physical self-motion induces it. To this end, 17 participants learned the layout of 9 irregularly arranged objects from one central learning orientation, and were subsequently blindfolded and asked to imagine facing new perspectives (120 or 240 degrees away from the learning orientation) and point “as accurately and quickly as possible” to the previously-learned target objects. As predicted, facing the new perspectives in an IMAGINE condition without physical self-motion was difficult and lead to increased response times, pointing errors, and configuration errors. Pointing and configuration errors improved, however, in a VECTION condition where participants experienced illusory self-rotation (circular vection) to the novel perspective, even though participants did not physically rotate. This illusory self-rotation was induced by combining rotating sound fields displayed via headphones (“auditory vection”) with biomechanical vection from stepping along a carrousel-like rotating floor platter that rotated in sync with the sound field. Perspective switch performance in the VECTION condition was not significantly different than performance in a REAL ROTATION condition, where blindfolded observers were physically rotated to the to-be-imagined perspective. The results show that perspective switches were facilitated by the illusion of self-motion in observers who were objectively stationary. They were facilitated to similar degrees for both illusory bipedal self-motion and for actual bipedal self-motion. This provides a promising method to facilitate the automatic and cognitive effortless forms of spatial updating that typically accompanies bipedal locomotion, without entailing the need for a large physical space or tracking system. Further research is needed, however, to generalize these findings and investigate if this facilitation of perspective switches resulted from reductions in sensorimotor interference (interference might arise from the conflict of the cues that specify stationarity and the original perspective on the one hand and the cues and instructions specifying a novel perspective on the other hand), from reduced cognitive transformation costs, or from a combination of these two factors.
Keywords: Riecke; Riecke_2014; daniel-feuereissen; john-rieser; spatial updating; talkWithoutPaper; timothy-mcnamara; vection